STRATEGI PENINGKATAN PELAYANAN AIR BERSIH DI KABUPATEN HALMAHERA TENGAH (Study PDAM Kota Weda) - Alhafiz, Isra; Lating, ALi; M.Djae, Raoda. (JOURNAL OF ETHNIC DIVERSITY AND LOCAL WISDOM, 2024)
Abstract The role of water is very important and has even become part of every human's life. Water is a basic need for humans that must always be available in everyday life, both for consumption, washing and bathing needs and so on. The availability of clean water is highly expected by the community to support daily life activities that cannot be separated from water needs, so in this case it needs to be supported by the existence of a professional body in managing water needs. The existence of the Tirta Halteng Regional Drinking Water Company is engaged in providing clean water needs which is one of the Regional Owned Enterprises (BUMD), so this company is known by the community as one of the sources in the management and provision of clean water. this research the researcher uses a qualitative descriptive approach and type of research, namely seeking information from the object that is the centre of the researcher either by obtaining sources from interviews, and documents. Based on the findings in the field, researchers found several sub-programmes in the strategy to improve clean water services, including the following: (1) Drinking water programme for low-income communities (MBR). (2) NUWSP/OPOR programme. (3) Network development cooperation in Weda City through the PUPR Office and PDAM. Researcher suggestions are: (1) There needs to be an effort from PDAM Central Halmahera Regency in improving the quality of clean water for the community. (2) in solving these problems and making it easier, the agencies concerned should be able to further improve and expand the existence of cooperation.